2010
DOI: 10.1080/15287391003689143
|View full text |Cite
|
Sign up to set email alerts
|

Depletion by Styrene of Glutathione in Plasma and Bronchioalveolar Lavage Fluid of Non-Swiss Albino (NSA) Mice

Abstract: Styrene is a widely used chemical, but it is known to produce lung and liver damage in mice. This may be related to oxidative stress associated with the decrease in the levels of reduced glutathione (GSH) in the target tissues. The purpose of this study was to investigate the effect of styrene and its primary metabolites R-styrene oxide (R-SO) and S-styrene oxide (S-SO) on GSH levels in the lung lumen, as determined by amounts of GSH in bronchioalveolar lavage fluid (BALF) and in plasma. When non-Swiss albino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Therefore, its loss due to oxidative stress or conjugation with styrene suggests adverse ramifications on cells like induction of apoptosis. One more study supported this claim where styrene (600 mg/kg) and its metabolites (300 mg/kg) significantly reduced GSH levels in broncho‐alveolar lavage (BAL) fluid and plasma . El‐Ziney et al used TBARS assay and showed very low doses of styrene (monostyrene) could increase LPO in female rats more than males.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, its loss due to oxidative stress or conjugation with styrene suggests adverse ramifications on cells like induction of apoptosis. One more study supported this claim where styrene (600 mg/kg) and its metabolites (300 mg/kg) significantly reduced GSH levels in broncho‐alveolar lavage (BAL) fluid and plasma . El‐Ziney et al used TBARS assay and showed very low doses of styrene (monostyrene) could increase LPO in female rats more than males.…”
Section: Discussionmentioning
confidence: 93%
“…One more study supported this claim where styrene (600 mg/kg) and its metabolites (300 mg/kg) significantly reduced GSH levels in broncho-alveolar lavage (BAL) fluid and plasma. 43 El-Ziney et al 44 used TBARS assay and showed very low doses of styrene (monostyrene) could increase LPO in female rats more than males. This may be due to the high conversion of this compound to its oxide forms in females rather than males.…”
Section: Discussionmentioning
confidence: 99%
“…These doses have been used in previous studies by us (Gadberry et al, 1996;Carlson, 1997Carlson, , 2010Carlson et al, 2006;Harvilchuck et al, 2008Harvilchuck et al, , 2009Meszka-Jordan et al, 2009). However, toxicity required lowering of these doses to 200 and 150 mg/kg respectively.…”
Section: Experimental Designmentioning
confidence: 95%
“…In a second pathway, styrene oxide is conjugated with glutathione (GSH). The mechanism of styrene-induced toxicity is not completely clear but may be related to oxidative stress (Harvilchuck et al, 2008(Harvilchuck et al, , 2009Meszka-Jordan et al, 2009), since styrene produces significant decreases in GSH levels in liver and lung as well as in plasma and bronchioalveolar lavage fluid (Carlson, 2010). This may in part be related to the conjugation of styrene oxide with GSH.…”
mentioning
confidence: 98%
“…Address correspondence to Gary P. Carlson (Carlson, 2010a). In a recent study, microsomal epoxide hydrolase (mEH -/-) knockout mice were found to be more susceptible than wild-type mice to styrene-induced hepatotoxicity, pneumotoxicity, and oxidative stress (Carlson, 2010b).…”
mentioning
confidence: 98%